2022
DOI: 10.1007/s00520-022-07502-8
|View full text |Cite
|
Sign up to set email alerts
|

A silence full of words: sociocultural beliefs behind the sexual health of Iranian women undergoing breast cancer treatment, a qualitative study

Abstract: Purpose Therapeutic interventions lead to impaired sexual health in women undergoing breast cancer treatment. There are some problem such as vaginal dryness, decreased libido, decreased sexual satisfaction, and decreased frequency of sexual intercourse among breast cancer survivors. This study was conducted to discover the sexual experiences of women undergoing breast cancer treatment. Methods A total of 39 semi-structured interviews were held with the women undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Because of surgery and other related treatments, BCPs would experience breast loss, surgical scar, alopecia, blackened and hardened nails, fatigue, decreased sexual desire, sexual dysfunction, and menopausal-like syndrome. 3 , 5 , 7 , 15 , 29 , 30 Patients usually believe that these symptoms destroy the identity of a traditional female, thereby affecting their external beauty and femininity, 26 damaging the normal function of the breast, reducing the hormone level, and finally, causing physiological dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…Because of surgery and other related treatments, BCPs would experience breast loss, surgical scar, alopecia, blackened and hardened nails, fatigue, decreased sexual desire, sexual dysfunction, and menopausal-like syndrome. 3 , 5 , 7 , 15 , 29 , 30 Patients usually believe that these symptoms destroy the identity of a traditional female, thereby affecting their external beauty and femininity, 26 damaging the normal function of the breast, reducing the hormone level, and finally, causing physiological dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that patients with lower socioeconomic status experience more sexual dysfunction and lower sexual frequency 13,32–34 . Patients of ethnic minority backgrounds may also feel uncomfortable accessing sexual health‐related services and completing sexual health surveys due to perceived irrelevance, cultural taboo, or fear of shame and judgment 3,16,35 . Thus, despite experiencing more sexual dysfunction than their counterparts, patients who are not married and have Medicare insurances may be overlooked in clinical care and in outcomes research.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Age and sociocultural barriers may hinder patients from freely discussing their sexual health with their providers. [14][15][16] Attitudes, experience, and interest regarding sexuality can also affect participants' willingness to partake in sexual health surveys. 17,18 Nonetheless, there is a paucity of information on missing data in sexual health surveys among breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in most Asian countries, including Iran, sexual issues are considered as taboo and talking about these issues is associated with feelings of shame and guilt. Health care providers are not exception, so there is not any communication about the sexual concerns between providers and patients [ 24 ]. In a study by Masjoudi et al, neglecting the sexual concerns of the survivors and the lack of teamwork among the service providers were two of the most important obstacles to talk about the sexual concerns of patients from the patient- provider communication perspective [ 25 ].…”
mentioning
confidence: 99%